The Effect of the Joyful Learning Method on the Third-Grade Students' Learning Outcomes in Mathematics - Selani Julia Habeahan; Patri Janson Silaban; Nova Florentina Ambarawati; Rumiris Lumbangaol; Darinda Sofia Tanjung (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
Students who have learning difficulty in mathematics learning subjects indicate unsatisfactory learning results and incomplete scores with KKM. The quantitative research method is a research method that is based on positive philosophy used to study the research instruments, and the data analysis is quantitative or statistical in order to test the hypotheses that have been set. The research method used is an experimental research method. The students' mathematics learning outcomes before being given treatment obtained an average value of 50.80. The result of the normality test was 0.128. Hence, it can be concluded that the pretest learning outcomes are normally distributed. The students’ mathematics learning outcomes after being given treatment obtained an average score of 72.69. The normality test result was 0.117. Hence, it can be concluded that the post-test learning outcomes are normally distributed. It can be proven that a correlation coefficient value of 0.846 is in the powerful interference category. The results of the T-test to find out whether the hypothesis is accepted or rejected are seen from the tcount 9,118 ≥ ttable 1,692, which means that there is an effect of Joyful Learning on students’ learning outcomes. Thus, Ha was accepted and Ho was rejected.